BRCA testing, treatment patterns and survival in platinum-sensitive recurrent ovarian cancer – an observational cohort study. Issue 1 (December 2016) - Unni, Sudhir; Schauerhamer, Marisa; Deka, Rishi; Tyczynski, Jerzy; Fernandes, Ancilla; Stevens, Vanessa; Brixner, Diana; Stenehjem, David
Abstract Background Breast cancer associated (BRCA ) genes are critical for DNA repair. Mutations inBRCA1 andBRCA2 (BRCA m) result in loss of these repair mechanisms and potential carcinogenesis. GermlineBRCA m are common in ovarian carcinomas, particularly in platinum-sensitive disease. The increased prevalence ofBRCA m in platinum-sensitive disease is likely due to enhanced responsiveness to platinum chemotherapy from homologous recombination repair deficiency. The purpose of this study was to exploreBRCA testing, treatment patterns and survival in platinum-sensitive recurrent (PSR) ovarian cancer. Methods This was an observational cohort analysis of PSR ovarian cancer treated at the Huntsman Cancer Institute from 1995 to 2012. GermlineBRCA status was ascertained through chart review and categorized asBRCA m (BRCA1/2 positive), BRCA wt (BRCA wild type or variant of uncertain significance), and untested. Treatment patterns and survival were assessed from recurrence until death or last follow-up. The Kaplan-Meier method was used to evaluate survival from recurrence byBRCA status. Logistic regression and COX proportional hazard model was used to estimate predictors ofBRCA testing and survival, respectively. Results Of the 168 PSR patients, 15 (9 %) wereBRCA m, 25 (15 %) wereBRCA wt, and 128 (76 %) were untested. Median age at PSR was 56 years forBRCA m andBRCA wt (p =  0.90) and 63 years for those untested (p =  0.033 vsBRCA m). Overall survival was similar betweenBRCA m andBRCA wt (median 50.4 vs 67.5 months, p =  0.86) and was 24.9 months in untested patients. Significant predictors for the likelihood ofBRCA testing were age (OR = 0.93, 95 % CI 0.89, 0.97, p  = 0.002), family history of breast or ovarian cancer (OR = 8.33, 95 % CI: 3.08, 22.59, p  < 0.001), and cancer diagnosis year (OR = 10.02, 95 % CI: 3.22, 31.21, p  < 0.001).BRCA -tested patients had a lower risk of death versus untested (HR 0.35, 95 % CI 0.17, 0.68, p  = 0.001). Conclusions BRCA wt patients had similar outcomes toBRCA m patients, potentially owing to similar age at diagnosis, representing aBRCA testing channeling bias. Younger patients, those with a family history of breast or ovarian cancer, and those diagnosed more recently were more likely to beBRCA tested. BRCA tested patients had a lower risk of death.